3D printing skills as a resource for the development of creativity in middle childhood = Umiejętności obsługi drukarek 3D jako zasób wspierający rozwój kreatywności w średnim dzieciństwie - Farnicka, Marzanna; Serrano Diaz, Noemi (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to describe the Dream Makers Project. The main objective of the project is to improve creative thinking and skills at the stage of pre-school education through 3D printing activities. The main concepts of this project are entrepreneurship education and training. This perspective is a well-established field of study that fosters entrepreneurial mindsets and skills which integrate socio-emotional aspects, such as self-confidence, leadership, creativity, motivation, resilience and self-efficacy.
Keywords: konstruktywizm; nierówności; innowacje; edukacja przedszkolna; umiejętności; constructivism; inequality; innovation; pre-school education; skills